Influence of a silica aerogel filler on the mechanical, thermal, and physical properties of flax/epoxy composite - Chandrasekar, M.; Shahroze, R. M.; Kumar, T. Senthil Muthu; Senthilkumar, K.; Ishak, M. R.; Rajini, N.; Siengchin, S. (Springer, 2022)
The influence of Maerogel (MA) on the material properties of the flax fiber reinforced epoxy composites has been investigated. The composites were fabricated using the hot press molding method with incorporation of MA, a kind of silica aerogel derived from the rice husk ash. The effect of different MA concentrations on the thermal, mechanical, and physical properties of flax/epoxy composites was investigated.